SciBet as a portable and fast single cell type identifier - Chenwei Li (Nature Portfolio, 2020)
The increasing size of single cell sequencing data sets calls for scalable cell annotation methods. Here, the authors introduce SciBet, which uses a multinomial distribution model and maximum likelihood estimation for fast and accurate single cell identification.